2019
DOI: 10.1021/acs.jpca.9b10121
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the OH-Initiated Oxidation of Mercury in the Global Atmosphere without Violating Physical Laws

Abstract: In 2005, Calvert and Lindberg wrote that the use of laboratory-derived rate constants for OH + Hg(0) "…to determine the extent of Hg removal by OH in the troposphere will greatly overestimate the importance of Hg removal by this reaction." The HOHg• intermediate formed from OH + Hg will mostly fall apart in the atmosphere before it can react. By contrast, in laboratory experiments, Calvert and Lindberg expected HOHg• to react with radicals (whose concentrations are much higher than in the atmosphere). Yet almo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 85 publications
2
56
1
Order By: Relevance
“…Mercury is a neurotoxin which is transported globally by the atmosphere . Mercury deposits from the atmosphere to ecosystems most efficiently when it is in the form of Hg­(II) compounds. , Unfortunately, we are still uncovering major aspects of the redox chemistry of atmospheric mercury. This complicates efforts to predict the impact of emissions reductions on the spatial distribution of mercury entry into ecosystems. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mercury is a neurotoxin which is transported globally by the atmosphere . Mercury deposits from the atmosphere to ecosystems most efficiently when it is in the form of Hg­(II) compounds. , Unfortunately, we are still uncovering major aspects of the redox chemistry of atmospheric mercury. This complicates efforts to predict the impact of emissions reductions on the spatial distribution of mercury entry into ecosystems. , …”
Section: Introductionmentioning
confidence: 99%
“…It is believed that atomic bromine is the major agent initiating oxidation of Hg(0). , Horowitz et al updated a global model of atmospheric mercury to incorporate recent advancements in the mechanism and kinetics of Hg(0) oxidation by gas-phase Br . They found oxidation to proceed so rapidly as to underpredict [Hg(0)], which inspired a search for reduction pathways to add to models.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation with OH radicals is an important pathway when considering the proportion of oxidation rates, consisting with previous studies (Selin et al, 2007;Shah et al, 2021). Indeed, recent research has found that the main products HOHg I and Hg(OH) 2 formed by the oxidation of Hg 0 by OH are relatively stable (Dibble et al, 2020). The reservoir of global atmospheric Hg is 3896 Mg, of which Hg 0 and Hg II are 3566 Mg and 330 Mg, respectively (for Hg II , 122 Mg and 208 Mg in the gaseous and particulate phases, respectively).…”
Section: Global Atmospheric Hg Budgetmentioning
confidence: 59%
“…Scientists currently believe that Hg(0) oxidation is mainly initiated by atomic bromine, to yield stable Hg­(II) compounds such as BrHgOH, BrHgOOH, and BrHgONO. ,, BrHgONO has two conformers (syn and anti) and an isomer (BrHgNO 2 ) . Photolysis of BrHgONO , and BrHgOOH can produce the radical BrHgO.…”
Section: Introductionmentioning
confidence: 99%
“…Photolysis of BrHgONO , and BrHgOOH can produce the radical BrHgO. Initiation of Hg(0) oxidation by hydroxyl radical leads to a Hg­(I) radical intermediate: HgOH . Goal of this paper is to investigate the monohydration of these seven mercury compounds.…”
Section: Introductionmentioning
confidence: 99%